Assessment of the toxic effect of pesticides on honey bee drone fertility using laboratory and semifield approaches: A case study of fipronil. (4th April 2017) - Kairo, Guillaume; Poquet, Yannick; Haji, Haïthem; Tchamitchian, Sylvie; Cousin, Marianne; Bonnet, Marc; Pelissier, Michel; Kretzschmar, André; Belzunces, Luc P.; Brunet, Jean‐Luc
Abstract: Concern about the reproductive toxicity of plant protection products in honey bee reproducers is increasing. Because the reproductive capacity of honey bees is not currently considered during the risk assessment procedure performed during plant protection product registration, it is important to provide methods to assess such potential impairments. To achieve this aim, we used 2 different approaches that involved semifield and laboratory conditions to study the impact of fipronil on drone fertility. For each approach, the drones were reared for 20 d, from emergence to sexual maturity, and exposed to fipronil via a contaminated sugar solution. In both groups, the effects of fipronil were determined by studying life traits and fertility indicators. The results showed that the survival and maturity rates of the drones were better under laboratory conditions than under semifield conditions. Moreover, the drones reared under laboratory conditions produced more seminal fluid. Although these differences could be explained by environmental factors that may vary under semifield conditions, it was found that regardless of the approach used, fipronil did not affect survival rates, maturity rates, or semen volumes, whereas it did affect fertility by inducing a decrease in spermatozoa quantity that was associated with an increase in spermatozoa mortality. These results confirm that fipronil affects drone fertility and support the relevance of each approach for assessing the potential reproductive toxicity of plant protection products in honey bees. Environ Toxicol Chem 2017;36:2345–2351. © 2017 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals, Inc. on behalf of SETAC.